Sequential Drug Release and Enhanced Photothermal and Photoacoustic Effect of Hybrid Reduced Graphene Oxide-Loaded Ultrasmall Gold Nanorod Vesicles for Cancer Therapy - Song, Jibin (ACS Nano, 2015)
We report a hybrid reduced graphene oxide (rGO)-loaded ultrasmall plasmonic gold nanorod vesicle (rGO-AuNRVe) (~65 nm in size) with remarkably amplified photoacoustic (PA) performance and photothermal effects. The hybrid vesicle also exhibits a high loading capacity of doxorubicin (DOX), as both the cavity of the vesicle and the large surface area of the encapsulated rGO can be used for loading DOX, making it an excellent drug carrier. The loaded DOX is released sequentially: near-infrared photothermal heating induces DOX release from the vesicular cavity, and an intracellular acidic environment induces DOX release from the rGO surface. Positron emission tomography imaging showed high passive U87MG tumor accumulation of (64)Cu-labeled rGO-AuNRVes (~9.7% ID/g at 24 h postinjection) and strong PA signal in the tumor region. Single intravenous injection of rGO-AuNRVe-DOX followed by low-power-density 808 nm laser irradiation (0.25 W/cm(2)) revealed effective inhibition of tumor growth due to the combination of chemo- and photothermal therapies. The rGO-AuNRVe-DOX capable of sequential DOX release by laser light and acid environment may have the potential for clinical translation to treat cancer patients with tumors accessible by light. [Image: see text]